Efficacy of endoscopic screening for esophageal cancer in China (ESECC): design and preliminary results of a population-based randomised controlled trial. Issue 2 (6th January 2018) - He, Zhonghu; Liu, Zhen; Liu, Mengfei; Guo, Chuanhai; Xu, Ruiping; Li, Fenglei; Liu, Anxiang; Yang, Haijun; Shen, Lin; Wu, Qi; Duan, Liping; Li, Xiang; et al.
Abstract : Objective: Description of the design and preliminary results of baseline recruitment and screening in the endoscopic screening for esophageal cancer in China (ESECC), the first randomised controlled trial (RCT) assessing efficacy and cost-effectiveness of endoscopic screening for esophageal squamous cell carcinoma (ESCC). Design: ESECC trial is a cluster RCT, and 668 villages in rural Hua County, Henan Province, a high-incidence area of ESCC in China, were randomised into two arms at a ratio of 1:1. Screening arm participants were screened by Lugol chromoendoscopy; no screening was performed in the control arm. ESCC-specific and all-cause mortality, incidence of advanced ESCC and cost-effectiveness of screening will be evaluated in the next 10-year follow-up. Here, we report the performance of baseline recruitment and randomisation, prevalence of upper GI lesions and risk factors for ESCC. Results: A total of 17 151 and 16 797 participants were enrolled in screening and control arms from January 2012 to September 2016. The truncated prevalence (aged 45–69 years) of oesophageal and overall upper GI high-grade lesions was 744.0/100 000 and 902.0/100 000. 69.9% of the 113 patients with high-grade oesophageal lesions were of early stage. Risk factors for severe oesophageal dysplasia and more severe lesions in this population included higher age, family history of ESCC, lower body mass index, eating rapidly and frequent ingestion of leftovers. Conclusion: This ESECC trial met the predesigned recruitment and randomisation requirements. Age, family history, undernutrition and unhealthy dietary habits increased the risk for high-grade oesophageal lesions in this high-risk population. Trail registration number: NCT01688908; Pre-results .